Unresected screen-detected ductal carcinoma in situ: Outcomes of 311 women in the Forget-Me-Not 2 study. (February 2022) - Maxwell, Anthony J.; Hilton, Bridget; Clements, Karen; Dodwell, David; Dulson-Cox, Joanne; Kearins, Olive; Kirwan, Cliona; Litherland, Janet; Mylvaganam, Senthurun; Provenzano, Elena; Pinder, Sarah E.; Sawyer, Elinor; et al.
Abstract: Background and aim: The natural history of ductal carcinoma in situ (DCIS) is poorly understood. The aim of this cohort study was to determine the outcomes of women who had no surgery for screen-detected DCIS in the 6 months following diagnosis. Methods: English breast screening databases were retrospectively searched for women diagnosed with DCIS without invasive cancer at screening and who had no record of surgery within 6 months of diagnosis. These were cross-referenced with cancer registry data. Details of the potentially eligible women were sent to the relevant breast screening units for verification and for completion of data forms detailing clinical, radiological and pathological findings, non-surgical treatment and subsequent clinical course. Results: Data for 311 eligible women (median age 62 years) were available. 60 women developed invasive cancer, 56 ipsilateral and 4 contralateral. Ipsilateral invasion risk increased approximately linearly with time for at least 10 years. The 10-year cumulative risk of ipsilateral invasion was 9% (95% CI 4–21%), 39% (24–58%) and 36% (24–50%) for low, intermediate and high grade DCIS respectively and was higher in younger women, in those with larger DCIS lesions and in those with microinvasion. Most invasive cancers that developed were grade 2 or 3. Conclusion: The findings suggest that active surveillance may be a reasonable alternative to surgery in patients with low grade DCIS but that women with intermediate or high grade disease should continue to be offered surgery. This highlights the importance of reproducible grading of DCIS to ensure patients receive appropriate treatment. Highlights: >1/3 women with intermediate/high grade DCIS developed invasive cancer within 10 years. Approximately 10% of women with low grade DCIS developed invasion within 10 years. Most invasive cancers that developed were grade 2 or 3. The risk of invasion was age-dependent and higher in younger women. Invasion risk was higher in larger DCIS lesions.